2012
DOI: 10.1073/pnas.1216988110
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CDKL5 disrupts kinome profile and event-related potentials leading to autistic-like phenotypes in mice

Abstract: Mutations in the X-linked cyclin-dependent kinase-like 5 (CDKL5) gene have been identified in neurodevelopmental disorders including atypical Rett syndrome (RTT), autism spectrum disorders (ASDs), and early infantile epileptic encephalopathy. The biological function of CDKL5 and its role in the etiology of these disorders, however, remain unclear. Here we report the development of a unique knockout mouse model of CDKL5-related disorders and demonstrate that mice lacking CDKL5 show autistic-like deficits in soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
247
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(286 citation statements)
references
References 54 publications
18
247
1
Order By: Relevance
“…Having a screening approach in mind, we tested well-characterized S/T phosphorylation motif antibodies, which detect all phosphorylated PKA/PKC substrates in brain lysates. 33 There is a global phosphorylation increase in the Injury compared with the Sham group (Figure 2a), which is in line with the notion that inflammatory and/or ischemic insults activate PKA/PKC signaling. [34][35][36] Importantly, we detected a further increase in phosphorylation in the Injury+sPIF compared with the Injury group, suggesting possible modulation of PKA/PKC signaling by sPIF.…”
supporting
confidence: 85%
“…Having a screening approach in mind, we tested well-characterized S/T phosphorylation motif antibodies, which detect all phosphorylated PKA/PKC substrates in brain lysates. 33 There is a global phosphorylation increase in the Injury compared with the Sham group (Figure 2a), which is in line with the notion that inflammatory and/or ischemic insults activate PKA/PKC signaling. [34][35][36] Importantly, we detected a further increase in phosphorylation in the Injury+sPIF compared with the Injury group, suggesting possible modulation of PKA/PKC signaling by sPIF.…”
supporting
confidence: 85%
“…To identify the minimal binding motif, we generated a series of N-terminal deletion mutants of PSD-95 with GFP fused to their C termini and tested their interaction with CDKL5. We observed that PSD-95 (amino acids 1-21), PSD-95 (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and PSD-95 (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] bound to CDKL5 at comparable levels (Fig. 2B).…”
Section: Psd-95mentioning
confidence: 79%
“…Loss-of-function studies using RNA interference (RNAi) revealed that CDKL5 is required for neurite growth and excitatory synapse stability (5,7). Deficiency of CDKL5 in mice leads to autistic-like phenotypes, indicating a causal role for CDKL5 loss of function in disease (8).…”
mentioning
confidence: 99%
“…CDKL5 knockdown in cultured hippocampal neurons results in aberrant spine morphology (Chen et al, 2010) and unstable dendritic spines . Intriguingly, the analysis of novel mouse models carrying Cdkl5 deletion showed alterations in sensory evoked potentials both in the auditory and the visual cortices (Wang et al, 2012, Amendola et al, 2014).In conclusion, Foxg1haploinsufficiency causes a severe impairment in visual function that is likely due to altered cortical mechanisms. This should be taken into account when Foxg1 +/Cre mice are used in behavioral experiments and when visual function is evaluated in patients carrying FOXG1…”
mentioning
confidence: 97%